Influence of Atmospheric Attenuation of Laser Beam on performance of Free Space Optics System (Journal of the College of Basic Education, 2022)
In this research the optical parameters that effect on the performance of the free space optics (FSO) system such as wavelength ,transmitted optical power, aperture averaging factor, and power margin for different paths links have been discussed. also the scintillation index caused by atmospheric turbulence and the atmospheric attenuation of laser beam due to the scattering by fog, mist, and haze have been discussed for these systems, the simulations are performed for a horizontal-path propagation of the Gaussian-beam wave and for two wavelengths 780 nm, and 1600 nm